Slices of the past: how events are temporally compressed in episodic memory. Issue 1 (2nd January 2022) - D'Argembeau, Arnaud; Jeunehomme, Olivier; Stawarczyk, David
ABSTRACT: Remembering everyday events typically takes less time than the actual duration of the retrieved episodes, a phenomenon that has been referred to as the temporal compression of events in episodic memory. Here, we review recent studies that have shed light on how this compression mechanism operates. The evidence suggests that the continuous flow of experience is not represented as such in episodic memory. Instead, the unfolding of events is recalled as a succession of moments or slices of past experience that includes temporal discontinuities—portions of past experience are omitted when remembering. Consequently, the rate of event compression is not constant but depends on the density of recalled segments of past experience.